(untitled) (Scientific journal of the Fergana State University, 2023)
The article is about the fact that based on the use of the potential of local authorities and non-profit organizations in the field of environmental protection, the article is aimed at the effective use of the potential of land plots with the help of science and new technologies and the relevance of the active use of environmentally friendly, resource-saving energy sources, as well as low-water crops and fruit trees, , the third is about the employment of the majority of those in the books "Iron", "women", "youth", about the training of the population in the agricultural sector and work at a cluster enterprise.